ELECTRO-OSMOTIC FRACTIONATION OF HYDROGEN ISOTOPES IN ELECTROLYTIC SOLUTIONS USING COMPOSITE PROTON-PERMEABLE MEMBRANES - Pushkar'ov, O.; Zubko, A.; Sevruk, I.; Dolin (Jr.), V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Based on the analysis of the features of electroosmotic processes that are implemented in proton-conducting membranes, the possibility of fractioning hydrogen isotopes in electrolytes formed using tritiated water (HTO) is estimated. The interaction of the solution with the membranes in their channels leads to polarization and partial dissociation of the electrolyte molecules. In water molecules, when protium is replaced by a heavy isotope of hydrogen, the energy of breaking of hydrogen bonds increases and the process of their dissociation proceeds predominantly according to the scheme: HTO ↔ H + + TO–. A part of the released protons can join water molecules to form the H3О+ ion. H3O+ and ТO– ions are more mobile than other singly charged ions. The main characteristic that determines the suitability of electroosmotic membranes to the fractionation of hydrogen isotopes is proton conductivity. The released protons have anomalously high mobility due to their small size, tunnel and relay movement through hydrogen bonds between adjacent polar groups in the channels of the proton-conducting membranes. To ensure high proton conductivity in the pores and channels of the membranes, modifying substances are fixed, which contain the groups: –ОН- , –NH2, –NH, –SH, –COOH, –SO3H, acid salts and oxides, containing surface proton-conducting groups. To create proton-conducting membranes, it is possible to use surface-modified β-alumina (β-Al2O3(H3O+)) and protonated (H3О+) montmorillonite with ionic conductivity (5103 – 4104 Оhm cm–1). The most effective are surface modifiers with negatively charged sulfonic groups. The imposition of an external electric field leads to the movement of ions in the electrolyte, which leads to a redistribution of the isotope ratio in the near-anode and cathode spaces.